Formation and Repair of Tobacco Carcinogen-Derived Bulky DNA Adducts - Hang, Bo (Journal of Nucleic Acids, 2010)
DNA adducts play a central role in chemical carcinogenesis. The analysis of formation and repair of smoking-related DNA adducts remains particularly challenging as both smokers and nonsmokers exposed to smoke are repetitively under attack from complex mixtures of carcinogens such as polycyclic aromatic hydrocarbons and N-nitrosamines. The bulky DNA adducts, which usually have complex structure, are particularly important because of their biological relevance. Several known cellular DNA repair pathways have been known to operate in human cells on specific types of bulky DNA adducts, for example, nucleotide excision repair, base excision repair, and direct reversal involving O6-alkylguanine DNA alkyltransferase or AlkB homologs. Understanding the mechanisms of adduct formation and repair processes is critical for the assessment of cancer risk resulting from exposure to cigarette smoke, and ultimately for developing strategies of cancer prevention. This paper highlights the recent progress made in the areas concerning formation and repair of bulky DNA adducts in the context of tobacco carcinogen-associated genotoxic and carcinogenic effects.